ASSESSMENT OF CLINICO-PATHOLOGICAL TOXICITY OF SOME INSECTICIDAL FORMULATIONS ON BROILER CHICKENS (Journal of Medical & Health Sciences Review, 2025)
Synthetic insecticides such as α-cypermethrin, spinetoram, and fenpyroximate are widely used in agricultural pest control but may pose health risks to non-target animals. The present study was designed to evaluate the clinico-pathological toxicity of these insecticidal formulations in broiler chickens following repeated intramuscular exposure. Sixty day-old Cobb broiler chicks were randomly divided into ten groups (one control and nine treated groups receiving lethal, sublethal, or superlethal doses of each insecticide). Doses (ml/kg BW) were: α-cypermethrin 0.005, 0.00625, 1.25; spinetoram 0.002, 0.004, 0.008; and fenpyroximate 0.0187, 0.0375, 0.075, administered once daily for 21 days into the breast muscle. Growth parameters (initial and final body weight, weight gain), absolute and relative organ weights and histopathological changes were evaluated at the end of the experiment. Absolute liver, heart, and brain weights were markedly reduced, while relative organ weights remained statistically unchanged. Histopathological examination revealed dose-dependent alterations, including hepatocellular degeneration and lymphocytic infiltration (spinetoram superlethal), right ventricular hypertrophy and hemorrhage (fenpyroximate superlethal), and severe neuronal degeneration with glial proliferation (α-cypermethrin superlethal). These findings indicate that repeated exposure to α-cypermethrin, spinetoram, and fenpyroximate induces growth retardation and organ-specific toxic lesions in broiler chickens, highlighting potential risks associated with misuse of insecticides in poultry environments and warranting further biochemical and molecular investigations to elucidate underlying mechanisms.